Elastic properties and frequency performance of a novel 3–0-type three-component composite. (26th April 2019) - Borzov, P. A.; Filippov, S. E.; Topolov, V. Yu.; Brill, O. E.; Panich, A. E.
Abstract: A three-component 3–0-type composite based on the ferroelectric PZT-type ceramic is studied to show the elastic properties and their links to the piezoelectric properties and resonance frequencies. The corundum ceramic is used as a component with a large elastic stiffness, and in the presence of this component, almost equal volume fractions of corundum mc and air pores mp are achieved at 0.05 <  mc < 0.18. This influences the elastic and other properties of the studied composite. Experimental results on its performance are interpreted in terms of a model wherein an interaction between the 3–0 ferroelectric ceramic/corundum and 3–0 ferroelectric ceramic/air regions plays the important role. A correlation between the elastic and piezoelectric anisotropy factors is observed, and the anisotropy of the piezoelectric coefficients d 33 * / d 31 *  ≈ −4 is stated at mc  > 0.10. The studied composite is of interest as an active element of piezoelectric transducers and sensors.